Traditional Turkish Coffee with Medicinal Effect - Senthil Rethinam; Serdar Batıkan Kavukcu; Hayati Türkmen; Arife Candaş Adıgüzel Zengin; İhsan Yaşa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Traditional Turkish coffee (TTC) is highly associated with caffeine and is known as a mind and heart stimulant as it helps keep tiredness at bay. Daily consumption of TTC naturally benefits human health such as anti-cancer, anti-diabetic, improved energy, anti-depression, reduced risk of heart disease, etc. The TTC was derived from particular types of Arabic coffee beans (ACB), and the preparation method of TTC is unique from other types of coffee. The main objective of the study was to investigate the therapeutic and biological effects of TTC. The ACB powder was characterized physicochemically using UV-Vis spectroscopy, Fourier transforms infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). In vitro analysis using HaCaT (Human keratinocyte cell line) proved the biocompatibility of ACB powder. Case studies which were focusing on healthy individuals as the research populace were conducted using TTC. Consumption of TTC was found beneficially compared to other types of coffee. The TTC was obtained from ACB, which was characterized by spectroscopic techniques and displayed biocompatibility due to the results on HaCaT cell lines. The TTC has beneficial therapeutic effects on individuals. According to statistical analysis, the disease-affected ratio of diabetes, heart disease, and depression was significantly decreased.